Margen de selectividad de varios herbicidas en la yuca - Doll, Jerry D.; Piedrahíta Castañeda, Wilson (1974)
Twenty-six herbicides were evaluated at 3 rates each in cassava (Manihot esculenta Crantz). For the 21 preemergence herbicides, planting was done before application in half the plot and then in the other half. After incorporating the 5 preplant-incorporated products, half the plot was ridged before planting while the remainder was planted without ridging. The recommended rate for heavy soils was applied, plus the double and quadruple of this rate, to establish the margin of selectivity. Injury ratings taken 30, 45, 60, 90 and 110 days after planting showed that the herbicides linuron, norea, fluometuron, chlorbromuron, diuron, fluoiodifen, nitrofen, pronamide, methazole, butachlor, alachlor, DNBP, chloramben, cyanazine, benthiocarb, trifluralin and nitralin were highly selective in cassava. Ametryne, prometryne, terbutryne and butilate had marginal selectivity: and atrazine, bromacil, karbutilate, EPTC and Vernolate were toxic even at the lowest rate, There was no increased toxicity by, planting before rather than after the application of the preemergence products nor by planting in ridged or in unridged soil after incorporating the preplant-incorporated compounds. (AS)